2016
DOI: 10.1016/j.jmb.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

ExoCarta: A Web-Based Compendium of Exosomal Cargo

Abstract: Exosomes are membranous vesicles that are released by a variety of cells into the extracellular microenvironment and are implicated in intercellular communication. As exosomes contain RNA, proteins and lipids, there is a significant interest in characterizing the molecular cargo of exosomes. Here, we describe ExoCarta (http://www.exocarta.org), a manually curated web-based compendium of exosomal proteins, RNAs and lipids. Since its inception, the database has been highly accessed (>54,000 visitors from 135 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
946
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,166 publications
(977 citation statements)
references
References 27 publications
23
946
1
7
Order By: Relevance
“…They contain common marker proteins such as tetraspanins (e.g., CD 9, CD 10, or CD 26), endosome-associated proteins (Alix, TSG101), cytoplasmic heat shock proteins, and-most important for cell-cell interaction-cell-type specific proteins and nucleic acids [69,70]. More than 40,000 proteins, 7500 RNA, and 1100 lipid molecules have been identified from more than 286 exosomal studies [71]. Exosome signaling seems to be promoted by interaction via unknown receptors on target cells inducing downstream signaling or via direct fusion of the exosomal membrane with the target cell membrane delivering their content into the cell [65,69,70,72].…”
Section: Exosome Signaling As a New Form Of Sec/hsc Crosstalkmentioning
confidence: 99%
“…They contain common marker proteins such as tetraspanins (e.g., CD 9, CD 10, or CD 26), endosome-associated proteins (Alix, TSG101), cytoplasmic heat shock proteins, and-most important for cell-cell interaction-cell-type specific proteins and nucleic acids [69,70]. More than 40,000 proteins, 7500 RNA, and 1100 lipid molecules have been identified from more than 286 exosomal studies [71]. Exosome signaling seems to be promoted by interaction via unknown receptors on target cells inducing downstream signaling or via direct fusion of the exosomal membrane with the target cell membrane delivering their content into the cell [65,69,70,72].…”
Section: Exosome Signaling As a New Form Of Sec/hsc Crosstalkmentioning
confidence: 99%
“…4) In fact, it was reported that exosomes contained both mRNA and microRNA (miRNA) that could be transferred to and be functional in target cells. 5) In addition, it was also suggested that exosomes could be distinctive biomarkers for diseases such as cancer and Alzheimer's disease.…”
mentioning
confidence: 99%
“…In fact, according to the ExoCarta database (35), many known exosome cargo proteins are also found in microvesicles, complicating studies on exosome cargo loading mechanisms. These observations, however, were largely based on experimental systems that captured a steady state profile of extracellular vesicles.…”
Section: Resultsmentioning
confidence: 99%